Art Students’ Error Analysis in Using Past Tense in Narrative Essay - Bardianing, Wahyun; Wirawati, Bekti; Surjowati, Ribut; Tria Shalsadita, Ratu; Auliya Soekandar, Amana; Arif Rizaldi, Septian (Universitas Nusantara PGRI Kediri, 2023)
As EFL learners, writing a narrative essay with proper grammatical rules and good chronological order is not easy. Although simple past tense has been introduced to students, previous studies found that the misuse of past tense remains a problem. A similar case also happened to art students at Sekolah Tinggi Kesenian Wilwatikta Surabaya. Thus, this study aimed to find out the students’ errors in using past tense in their narrative essays. It is seen as an urgent point since the literature about how art students deal with English subjects is very limited. Help is still required, and it begins by identifying their errors in writing. By employing qualitative content analysis of 30 students’ narrative essays, this study found a total of 197 errors. These errors were grouped into three categories: omission (98 errors), addition (67 errors), and misinformation (32 errors). A conclusion was drawn that the students committed grammatical errors in their narrative essays due to several factors such as L1 interference, different grammatical rules between Indonesia and English, insufficient grammatical knowledge, overgeneralization, rule restriction ignorance, and false hypothesis.